Integrating Infant Massage and Aromatherapy as a Complementary Non-Pharmacological Intervention in Supporting Infant Growth and Development - Darah Ifalahma; Totok Wahyudi; Cindy Octavia; Risma Nurul Istiqomah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Early childhood is a critical period for growth and development, characterized by rapid changes in neurological, motor, sensory, and emotional systems. Stimulation during this stage plays a vital role, and non-pharmacological interventions such as massage and aromatherapy may enhance developmental outcomes. This quasi-experimental study employed a pretest–posttest control group design to evaluate the effectiveness of infant massage combined with aromatherapy. Twenty infants aged 3–12 months who met inclusion and exclusion criteria were recruited and assigned to either a control group (infant massage only) or an intervention group (infant massage with aromatherapy). Growth parameters (weight, length, head circumference) and developmental outcomes were measured using the Developmental Pre-Screening Questionnaire, covering gross motor, fine motor, language, and personal-social domains. Infants in the intervention group demonstrated significantly greater improvements in body weight, body length, head circumference, and developmental scores compared to the control group. These findings indicate that the addition of aromatherapy to infant massage provides measurable benefits for both physical growth and developmental progress. Combined infant massage and aromatherapy represent effective non-pharmacological strategies for early stimulation, supporting optimal growth and developmental trajectories in infants.